Pelaksanaan Pengawasan Serta Penegakan Hukum Keimigrasian Dalam Pelanggaran Keimigrasian Overstay - Chrisna Erlangga Surbakti; Deozzy Anugerah Pratama; Ferdyan Asgar (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Indonesia is a country that is a tourist center for foreigners from various countries. This is supported because Indonesia has a wealth and stunning natural charm that makes Indonesia an attraction to become a tourist destination. Seeing this potential, the Indonesian government facilitates access to enter the country of Indonesia. But in reality, the kindness of the Indonesian government was abused by these foreigners. Many of the immigration violations they committed while in Indonesia, such as staying beyond a predetermined time limit or often called Overstay. In handling these cases, the government made various efforts in dealing with the problem of immigration violations. Supervision of foreigners is a form of effort by the government in terms of handling Overstay cases carried out by foreigners in Indonesia. In its implementation, the government also enforces the law against foreigners who commit Overstay violations so as to reduce the number of violations.